1981
DOI: 10.1177/0272989x8100100405
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Screening for Hepatitis B Surface Antigen in India

Abstract: We have developed a quantitative model to study the impact of screening for the hepatitis B surface antigen using either second-generation (counterimmunoelectrophoresis) or third-generation (radioimmunoassay) tests. This model was fashioned for general use but was applied to data on hepatitis for India, in an attempt to determine what factors would most influence the decision to institute a screening program for the surface antigen in that country. Screening for the surface antigen should reduce post-transfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…With one-way analysis, each uncertainty component of the evaluation is varied individually, while the others are held at their baseline values, in order to establish the separate effect of each component on the results of the evaluation. For example, in a cost-effectiveness analysis of a screening programme for hepatitis B surface antigen in India, 64 the authors carried out a one-way sensitivity analysis on all variables, which they illustrated graphically by plotting the effectiveness and cost results against a range of each of the uncertain variables. It has been argued that a set of one-way analyses such as these may be sufficient if each of the uncertain variables is independent of the others.…”
Section: Simple Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…With one-way analysis, each uncertainty component of the evaluation is varied individually, while the others are held at their baseline values, in order to establish the separate effect of each component on the results of the evaluation. For example, in a cost-effectiveness analysis of a screening programme for hepatitis B surface antigen in India, 64 the authors carried out a one-way sensitivity analysis on all variables, which they illustrated graphically by plotting the effectiveness and cost results against a range of each of the uncertain variables. It has been argued that a set of one-way analyses such as these may be sufficient if each of the uncertain variables is independent of the others.…”
Section: Simple Sensitivity Analysismentioning
confidence: 99%
“…In the analysis of a screening programme for hepatitis B surface antigen referred to above, 64 the authors reported, for each variable in their model, a partial derivative which, when multiplied by a change in a given parameter, generated the impact on costs and effectiveness results. They also suggested an alternative measure based on elasticities that can be applied when it is not possible to calculate partial derivatives.…”
Section: Simple Sensitivity Analysismentioning
confidence: 99%